FAKTOR PENGHAMBAT KEANGGOTAAN TAIWAN DI INTERNATIONAL CIVIL AVIATION ORGANIZATION (ICAO) - Rizdyanthi, Kadek Wiendy; Widya Nugraha, A.A. Bagus Surya; Putri, Penny Kurnia (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2024)
This research aims to understand the factors that hinder Taiwan's involvement and membership in ICAO. The author uses a qualitative method with the theory of decision-making through the perspective of international organizations to analyze the issue. Decision-making ICAO is influenced by internal factors, namely the Chicago Convention, ICAO Council Members, ICAO President and General Secretariat, and ICAO Assembly.  External factors include the China-Taiwan Conflict, Taiwan's sovereign status, and Taiwan's territorial security. BInternalfactors and external factors have a relationship to influence each other in determining decisions. In internal factors, the Chicago Convention is used as a basic rule or determinant in every ICAO decision-making while external factors, namely the status of Taiwan's existence and its relationship with China are internal benchmarks in determining decisions. Thus, the results of this study explain that the relationship between these factors influences ICAO's decision not to re-engage Taiwan into the organization, even though Taiwan is said to have met the ideal criteria to be able to join ICAO or become part of ICAO. Keywords: Decision Making, ICAO,  International Organization, Taiwan,